Energy expenditure, growth, and nutritional therapy in appropriate and small for gestational age preterm infants - Andrea Dunshee de Abranches; Fernanda Valente Mendes Soares; Letícia Duarte Villela; Maria Dalva Barbosa Barker Méio; Olivia Araújo Zin; Saint‐Clair Gomes Junior; Maria Elisabeth Lopes Moreira (Brazilian Society of Pediatrics, 2018)
Objective: To evaluate the resting energy expenditure, growth, and quantity of energy and macronutrients intake in a group of preterm newborns. Methods: The cohort study was performed with appropriate and small for gestational age preterm infants (birth weight lower than 1500 g or gestational age < 32 weeks). Resting energy expenditure was measured using indirect calorimetry on the 7th, 14th, 21st, and 28th days of life, and at discharge. Length, head circumference and body weight were assessed weekly. Nutritional therapy was calculated during the hospital stay and the information for each type of food was recorded in software that calculates the total amount of energy and macronutrients. Results: 61 preterm infants were followed; 43 appropriate and 18 small for gestational age infants. There was no statistical difference for resting energy expenditure between the groups, and it increased from the first to the fourth week of life (appropriate: 26.3% and small: 21.8%). Energy intake in the first two weeks of life was well below the energy requirement. Conclusion: Considering that the results demonstrate high energy expenditure during the first weeks of life, there is an evident need to provide the best quality of nutrition for each child in the first weeks of life so that preterm infants with or without intrauterine growth restriction can achieve their maximum potential for growth and development. Resumo: Objetivo: Avaliar o gasto energético de repouso, o crescimento e a quantidade ofertada de energia e macronutrientes em um grupo de recém‐nascidos pré‐termo. Método: Foi feito estudo de coorte com recém‐nascidos pré‐termo adequados e pequenos para a idade gestacional (peso de nascimento inferior a 1.500 gramas ou idade gestacional < 32 semanas). O gasto energético foi avaliado com a calorimetria indireta nos dias 7°, 14°, 21°, 28° dias de vida e alta hospitalar. Medidas do comprimento, perímetro cefálico e peso corporal foram avaliadas semanalmente. A terapia nutricional foi calculada durante a internação do recém‐nascido e as informações de cada tipo de alimentação foram registradas em um software que calcula a quantidade total de energia e macronutrientes. Resultados: Foram acompanhados 61 recém‐nascidos, sendo 43 adequados e 18 pequenos para idade gestacional. O gasto energético de repouso não apresentou diferença estatística entre os grupos e aumentou entre a primeira e quarta semana de vida (adequados: 26,3% e pequenos: 21,8%). O aporte energético nas duas primeiras semanas de vida mostrou‐se bem abaixo do requerimento energético mensurado pela calorimetria. Conclusão: Considerando os resultados que demonstram um gasto energético alto ao longo das primeiras semanas de vida, fica evidente a necessidade de fornecer ao recém‐nascido pré‐termo um melhor aporte energético já nas primeiras semanas de vida, para que os neonatos com ou sem restrição intrauterina possam atingir o seu potencial máximo de crescimento e desenvolvimento. Keywords: Resting energy expenditure, Preterm infants, Nutritional therapy, Nutritional status, Palavras‐chave: Gasto energético, Recém‐nascido pré‐termo, Terapia nutricional, Estado nutricional